(untitled) (CIPEEX, 2025)
Medical students are susceptible to the problem of improper self-medication because they have a heavy workload. In addition, they have greater access to medical information. These factors influence students to self-medicate instead of seeking specialized care. The objective of this study is to verify the influence of knowledge acquired by medical students on self-medication. The study is a systematic review of the literature. Articles in Portuguese and English published between 2018 and 2024 were included, excluding all studies that used secondary data and data prior to 2018. The practice of self-medication is prevalent in academic settings, with alarming rates of up to 92.7%. The relationship between progress in medical school and the frequency of self-medication is evident, highlighting a significant increase as students progress through their academic cycles. This behavior not only reflects a false sense of security generated by the acquired knowledge but also leads to considerable side effects, such as nausea, cardiorespiratory symptoms, and the worsening of clinical conditions.